Early Roman fine wares from the pottery assemblage found in a cistern in the Agora of Nea Paphos, Cyprus - Kajzer, Małgorzata (Rei Cretariae Romanae Fautorum Acta, 2022)
The Agora of Nea Paphos, Cyprus has been investigated by the team from the Jagiellonian University since 2011. During the second year of excavations, in 2012, in the central part of the area, researchers found the structure interpreted as a cistern. The pottery assemblage discovered inside, dated to the Early Roman period, was not large, however it represents a variety of wares. The fine wares from this group of finds are characterised in the paper, as the representative sample of the pottery found in the site, dated to that period. Beside the table pottery (Eastern Sigillata A, B, D, Italian-type sigillata, lead-glazed ware), oil lamps representing the fine ware as well, were included.